Analisis Yuridis Tentang Pencemaran Nama Baik : Studi Kasus Luhut Binsar Pandjaitan - Stevanno Sebastian Entoh; Sari Mandiana; Jusup Jacobus Setyabudhi (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2024)
This research discusses the defamation that has been committed by Haris Azhar (HA) and Fatiah Maulidyianti (FM) who in one of their YouTube video uploads entitled 'There is a Lord Luhut Behind the Economic-OPS Military Relations of Intan Jaya!!! General BIN Also There!! NgeHAMtam' has defamed and caused false suspicion against Luhut Binsar Pandjaitan. It is known that HA and FM called Luhut 'lord'. Luhut also said that material losses do not need to be calculated, but morally, accusing me of being a criminal and being called a 'lord' is very detrimental to him and his family. This research will also discuss the defamation by Haris and Fatiah when viewed from the Criminal Code (KUHP), and Law Number 11 of 2008 which has been amended by Law Number 19 of 2016. This research uses normative / dogmatic juridical research methods. This research uses primary legal materials and secondary legal materials as the legal basis for completing this research. This research also uses the Statue Approach (approach through legislation), Conceptual Approach (conceptual approach), and Case Approach (case approach). In the results of this study, it can be concluded that the actions of HA and FM can be categorized as defamation because they have fulfilled the elements of Article 311 of the Criminal Code on slander and Article 318 of the Criminal Code on false suspicion. The advice in the form of legal opinion is that the prosecutor should be able to provide charges to HA and FM related to Article 311 of the Criminal Code on slander and Article 318 on false pretenses because this can later become the basis for the Judge's decision following the prosecutor's indictment.